2004
DOI: 10.1097/00000542-200403000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Produces Delayed Preconditioning against Myocardial Ischemia and Reperfusion Injury

Abstract: The results indicate that the volatile anesthetic isoflurane produces a second window of preconditioning against myocardial ischemia and reperfusion injury. Furthermore, COX-2 is an important mediator of isoflurane-induced delayed preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 21 publications
4
72
0
3
Order By: Relevance
“…In addition to a sufficient revascularization, elective myocardial protection is needed for the ventricular function to be maintained. There are various factors affecting postoperative myocardial function and extent of myocardial injury (6,7). Despite the great number of studies conducted, the mechanism of action of volatile anesthetic agents with regard to myocardial injury is not entirely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a sufficient revascularization, elective myocardial protection is needed for the ventricular function to be maintained. There are various factors affecting postoperative myocardial function and extent of myocardial injury (6,7). Despite the great number of studies conducted, the mechanism of action of volatile anesthetic agents with regard to myocardial injury is not entirely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…На сегодня известна роль ЦОГ 2 в реализации эффектов поздней фазы ишемического прекондиционирования, а инги биторы этого фермента, которые в последнее время нашли ши рокое применение в клинической практике, могут блокировать защитные эффекты как ишемического, так и анестетического прекондиционирования [29].…”
Section: блокада ишемического и фармакологического прекондиционированияunclassified
“…Among these agents, several studies show that the halogenated anesthetics are capable of promoting post-conditioning directly, or increasing indirectly the ischemic pre-and postconditioning against ischemia and reperfusion injuries 12,14,17 . This mechanism is not totally clear yet, but is seems to mimic ischemic pre-conditioning.…”
Section: Anesthetic Pre-and Post-conditioningmentioning
confidence: 99%
“…Nowadays it is quite evident that the effect is actually direct, and it involves the activation of various intracellular pathways that will promote protection against dysfunction and myocardial necrosis. Both the ischemic and the anesthetic pre-conditioning in the heart present the same cellular mechanism, which involves the activation of the mitochondrial and sarcolemma K ATP -dependent channels, resulting in overload decrease in the mitochondrial and myoplasmatic calcium 7,[17][18][19] . Additionally, studies have shown that the halogenated anesthetics promote protection against ischemia-reperfusion injuries by pre-conditioning blood vessels, protecting against vascular injuries and impeding the endothelium contribution to the pro-inflammatory and thrombogenic events related to ischemia-reperfusion injuries 20 .…”
Section: Anesthetic Pre-and Post-conditioningmentioning
confidence: 99%